Factorising Double Brackets 2

Easy

Medium

Difficult

Q1) \(x^2 + x -12 =\)
Q1) \(x^2 -144 =\)
Q1) \(6 x^2 + 7 x+ 2= \)
Q2) \(x^2 + 3x -10 =\)
Q2) \(x^2 -36 =\)
Q2) \(8 x^2 + 22 x+ 5= \)
Q3) \(x^2 + 4x -12 =\)
Q3) \(x^2 -121 =\)
Q3) \(4 x^2 + 8 x+ 3= \)
Q4) \(x^2 -x -6 =\)
Q4) \(x^2 -81 =\)
Q4) \(6 x^2 + 11x+ 3= \)
Q5) \(x^2 + 5x -24 =\)
Q5) \(4x^2 -49 =\)
Q5) \(9 x^2 + 12 x+ 4= \)
Q6) \(x^2 + 3x -28 =\)
Q6) \(x^2 -64 =\)
Q6) \(6 x^2 + 13 x+ 5= \)
Q7) \(x^2 + x -6 =\)
Q7) \(x^2 -9 =\)
Q7) \(4 x^2 + 12 x+ 5= \)
Q8) \(x^2 + 7x -18 =\)
Q8) \(9x^2 -100 =\)
Q8) \(8 x^2 + 10 x+ 3= \)
Q9) \(x^2 -2x -3 =\)
Q9) \(x^2 -4 =\)
Q9) \(9 x^2 + 15 x+ 4= \)
Q10) \(x^2 -6x -16 =\)
Q10) \(x^2 -25 =\)
Q10) \(8 x^2 + 14 x+ 5= \)